SEISMIC TERRITORIES AND IN THE TERRITORIES UNDER CONSTRUCTION TO BUILDINGS AND STRUCTURES WEARABLE REQUIREMENTS - Pakhirdinov Habibillo Zukhridinovich; Pulatova Extiborkhan free daughter (Bright Mind Publishing, 2025)
This in the article earthquake during building and to buildings seismic impact, soil movement, seismic vibration intensity, plot soil particles three arrow along in space movement, structure in the elements elasticity limit, strength from the border big was voltages, structures constructions deformation, vibrations appearances, structures injury and violations, private vibrations frequency (or vibration period), vibration uniforms building or building features, earthquake real building during vibration movement of energy dissipation process, building and buildings earthquake force (seismic forces ) durable as construction, earthquake-resistant building, structures design, earthquake-resistant structures, reinforced concrete with frame buildings construction, metal structures, exterior walls for light suspension panels , seismic in the regions under construction building, structures design in the process them additional accordingly seismic forces to the effect calculation.
Keywords: Earthquake, seismology, earthquake-prone areas, seismic zones, deformations.